Problematika Konflik Dalam Menjalin Hubungan Antar Sesama Manusia - Kasron Nasution (Hikmah, 2015)
Human-being born has special character so that there is nobody born really identic. Everyone depent on his character, that’s why everyone just think what he likes or dislikes and never thinking eventhougt it’s right or wrong. Someone who lives in his invironment always useless or distrub him, and other people always makes something wrong and deterrent his carier. It’s the reason that conflic always be happen. Talking about the conflic there are some profits and ferruginous cause of conflic. Conflic happen by the self interest be in contradiction according to the human desire. Not all conflic be bad, some people realize that the important one is how to overcome the conflic. Conflic can cause awareness to overcome problems and makes someone be honesty and be better.